Introduction to Surgery for Students - Fisher, Rebecca A.; Ahmed, Kamran; Dasgupta, Prokar; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides a one-stop guide to the basics of surgery for surgical rotations, as well as information for aspiring surgeons on how to explore a surgical career and build your CV for surgical applications. It is the perfect go-to companion for any student shadowing in theatres, and a thorough guide for students wishing to spend more time in a specific specialty, conduct research and plan careers. Introduction to Surgery for Students is an edited collection of 31 chapters from a group of 80 medical students, junior doctors and consultant surgeons. Each chapter is written by a team made up of at least one student and one senior, and then edited and reviewed by a medical student with a special interest in the topic. This near-peer style of writing allows the content to cater to a student$1 (Bs needs at the right level, whilst having the expert input of surgeons who are leaders in their field. .s
1. The history of surgery -- 2. Anatomy for surgeons -- 3. Radiology for surgeons -- 4. Role of the surgeon -- 5. Preoperative care -- 6. Anaesthetics -- 7. Perioperative care -- 8. Patient safety -- 9. Preparing the surgeon -- 10. Post-operative care -- 11. Minimally invasive surgery (MIS) -- 12. Principles of Surgical oncology and pathology -- 13. Neurosurgery -- 14. Ophthalmology -- 15. ENT surgery -- 16. Oral and maxillofacial surgery -- 17. Cardiothoracic surgery -- 18. Vascular surgery -- 19. General and emergency surgery -- 20. Urology -- 21. Orthopaedic Surgery -- 22. Plastic Surgery -- 23. Obstetrics and gynaecology -- 24. Paediatric surgery -- 25. Transplantation and immunology -- 26. I want to be a surgeon - what next? -- 27. Surgical research -- 28. Surgical Training, Simulation and Assessment -- 29. Careers -- 30. International careers - Training and working abroad -- 31. The NHS and private healthcare.
Keywords: Medicine; Surgery; Premedical education; Medicine & Public Health; General Surgery; Premedical education